Middle managers response to implementing the Employment Equity Act 55/1998 - Mojela, Mathapelo Magdeline (My University, 2008)
ABSTRACT The broad aim of this study was to explore how middle management in the banking sector is implementing and responding to the Employment Equity Act 55/98. The study was conducted at two organisations from the banking sector operating in the city of Johannesburg in 2005. The study focussed on understanding of employment equity act, implementation of the Employment Equity Act 55/98, organisational support and the broader impact of Employment Equity Act 55/98. The rationale was to gauge the challenges faced in transforming the workplace in terms of employment equity. This study utilised quantitative research design, specifically the subtype exploratory descriptive. The sample of the study comprised of 28 respondents, 18 drawn from Org A and 10 drawn from Org B. Respondents hold middle management positions in their organisations. Purposive sampling was employed for the selection of the respondents. Data was collected through semi structured interview schedules that were individually administered to each respondent by the researcher. Data was analyzed quantitavely and descriptively using tables and themes. The study revealed that the two organisations were employing different strategies in the implementation of the Act, i.e. not all middle managers are actively involved in the implementation of the Act and that different methods are used to motivate managers to achieve numerical targets. The study also revealed that the most or common challenge in the implementation of this Act is the lack of skills from the black people as defined by the said Act. The study concludes that, it will take longer period in achieving equity among the workforce, especially within smaller organisations as there is a great need to upgrade skills of black individuals and retaining them. Therefore, it recommends that organisations develop a workforce culture on how to develop and empower staff on different levels of hierarchy and how to retain them.